Effects of Weight Loss on Endothelium and Vascular Homeostasis: Impact on Cardiovascular Risk - Margherita Tiezzi; Francesco Vieceli Dalla Sega; Paolo Gentileschi; Michela Campanelli; Domenico Benavoli; Elena Tremoli (Biomedicines, 2025)
Available knowledge shows that obesity is associated with an impaired endothelial function and an increase in cardiovascular risk, but the mechanisms of this association are not yet fully understood. Adipose tissue dysfunction, adipocytokines production, along with systemic inflammation and associated comorbidities (e.g., diabetes and hypertension), are regarded as the primary physiological and pathological factors. Various strategies are now available for the control of excess body weight. Dietary regimens alone, or in association with bariatric surgery when indicated, are now widely used. Of particular interest is the understanding of the effect of these interventions on endothelial homeostasis in relation to cardiovascular health. Substantial weight loss resulting from both diet and bariatric surgery decreases circulating biomarkers and improves endothelial function. Extensive clinical trials and meta-analyses show that bariatric surgery (particularly gastric bypass) has more substantial and long-lasting effect on weight loss and glucose regulation, as well as on distinct circulating biomarkers of cardiovascular risk. This review summarizes the current understanding of the distinct effects of diet-induced and surgery-induced weight loss on endothelial function, focusing on the key mechanisms involved in these effects.